2018
DOI: 10.1136/bmjopen-2018-021879
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing rapid progress in child health in post-conflict Liberia: a mixed methods country case study on progress in child survival, 2000–2013

Abstract: ObjectivesOnly 12 countries in the WHO’s African region met Millennium Development Goal 4 (MDG 4) to reduce under-five mortality by two-thirds by 2015. Given the variability across the African region, a four-country mixed methods study was undertaken to examine barriers and facilitators of child survival prior to 2015. Liberia was selected for an in-depth case study due to its success in reducing under-five mortality by 73% and thus successfully meeting MDG 4. Liberia’s success was particularly notable given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Case studies from other post-conflict settings, such as Rwanda, Liberia, and Afghanistan, have shown that MoH leadership and the implementation of governance and accountability mechanisms are key determinants to strengthen health systems, increase the coverage of utilization of health services, and improve maternal and child health outcomes [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Case studies from other post-conflict settings, such as Rwanda, Liberia, and Afghanistan, have shown that MoH leadership and the implementation of governance and accountability mechanisms are key determinants to strengthen health systems, increase the coverage of utilization of health services, and improve maternal and child health outcomes [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Four SSA countries (Liberia, Zambia, Kenya and Zimbabwe) were chosen based on their U5M ARR between 1990 and 2011 (data available when the study was designed, Figure 1) and their national governments’ willingness to participate. Detailed study methods for each country case study have been published (Kipp et al ., 2016; Brault et al ., 2017, 2018; Haley et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We previously conducted country-specific case studies of four SSA nations with different annual rates of reduction (ARR) in U5M to identify specific barriers and facilitators that influenced their progress towards MDG#4 (Figure 1) (Kipp et al ., 2016; Brault et al ., 2017, 2018; Haley et al ., 2017). Liberia and Zambia were on track for MDG#4 when the study began (and have now met MDG#4) while Kenya and Zimbabwe were not on track (and did not meet MDG#4) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitations of health information systems in these countries [8] and quantitative indicator data to provide more nuanced understanding [9], we triangulated data from a policy review, qualitative key informant interviews with stakeholders working at multiple levels of the health system, and focus groups with women accessing services for their children (see supplemental file for interview and focus group discussion guides). Countries were chosen based on their U5M ARR between 1990 and 2011 (data available at the study's onset) and their health ministries' willingness to participate [10][11][12][13][14]. Two nations, Liberia and Zambia, were selected by our team because they were on track to achieve MDG4 in 2013 when the study was initiated (both countries did, ultimately, meet MDG4).…”
Section: A Summary Of Key Findingsmentioning
confidence: 99%
“…Two nations, Liberia and Zambia, were selected by our team because they were on track to achieve MDG4 in 2013 when the study was initiated (both countries did, ultimately, meet MDG4). In Liberia, we found the following factors to be critical to their reduction of U5M: national prioritization of MNCH after the civil war combined with continuous review and updates to key strategies; implementation of integrated services in facilities that expanded intervention access and promoted intersectoral collaboration; and use of outreach campaigns, community health workers and trained traditional midwives to expand access to care and improve referrals [15]. In Zambia, we found qualitative evidence of the benefits of Zambia's ongoing and long-term national health reform focused on ensuring universal access to MNCH care, specifically through strong community health strategies and service delivery approaches as well as positive and well-coordinated relationships with external partners [14].…”
Section: A Summary Of Key Findingsmentioning
confidence: 99%